The marital relationship and health‐related quality of life of prostate cancer patients and their spouses: A prospective, longitudinal study. Issue 6 (15th August 2022) - Harju, Eeva; Rantanen, Anja; Helminen, Mika; Kaunonen, Marja; Isotalo, Taina; Åstedt‐Kurki, Päivi
Abstract: Aims: This study aims to measure any changes in the marital relationship during the first year after a diagnosis of prostate cancer, identify the demographic characteristics that influenced such changes, and measure changes related to health‐related quality of life (HRQoL). Background: Knowledge is limited on the impact of a diagnosis of prostate cancer on the marital relationship and HRQoL of patients and their spouses. Design: A 1‐year longitudinal study. Methods: Data were collected from five Finnish hospitals between October 2013 and January 2017. Of the 350 recruited couples ( N  = 700), 179 patients and 166 spouses completed the Marital Questionnaire and the RAND 36‐Item Health Survey 1 year after diagnosis. Results: No major changes were found in the marital relationship during the follow‐up period. The spouses reported statistically significant changes in their marital relationships, but the patients did not. Furthermore, changes in the marital relationship were not associated with the patients' HRQoL. Among spouses, emotional well‐being was associated with changes in the marital relationship. Conclusion: The marital relationship was relevant in terms of the spouses' HRQoL during the first year after a diagnosis of prostate cancer. Nurses and other healthcare providers should assess counselling and support provided to spouses individually. Summary statement: What is already known about this topic? Prostate cancer affects not only the individual but also the whole family's structure and hierarchy. Prostate cancer patients' quality of life is better if their spouses have positive beliefs about the disease's duration and treatment control. What does this paper add? Spouses reported statistically significant changes in the marital relationship, but the patients did not. Among spouses, emotional well‐being was associated with changes in the marital relationship. This paper's implications: By individually assessing counselling and support to spouses during prostate cancer care, nurses and other healthcare providers have the opportunity to use these findings.